Anmeldelser - Moe, Bjarke (Danish Yearbook of Musicology, 2011)
Review of: Erik Kjellberg (ed.): The Dissemination of Music in Seventeenth-Century Europe. Celebrating the Düben Collection. Proceedings from the International Conference at Uppsala University 2006. Varia Musicologica, 18; Bern: Peter Lang Verlag, 2010.